Response of Soil Microbial Community Structure Mediated by Sulfur-Induced Resistance Against Kiwifruit Bacterial Canker - Yang, Sen; Shu, Ran; Yin, Xianhui; Long, Youhua; Yuan, Jun (Frontiers in Microbiology, 2022)
Kiwifruit bacterial canker caused by Pseudomonas syringe pv. actinidiae is a major threat to kiwifruit worldwide. Our previous study showed that sulfur could induce kiwifruit resistance to bacterial canker disease, but its possible influence on the kiwifruit ecosystem should be investigated, including the surrounding microbial community. In this study, the six content of sulfur treatments were tested for their influence on the rhizosphere microbial composition. Fertilization treatments of kiwifruit vine with sulfur and organic fertilizer resulted in a reduction in kiwifruit bacterial canker severity. Sulfur application in the range of 1.0~2.0 kg/m3 effectively increased the diversity and abundance of soil microbial communities. In particular, the bacterial genera level showed a high diversity after applying sulfur for two years, reaching more than 516 genera. Furthermore, sulfur treatment resulted in a significant increase in specific microbial taxa, including members of the Acidothermus, norank_f__HSB_OF53-F07 and norank_f __Acidobacteriaceae__Subgroup_1. Moreover, the proportion of the dominant bacteria Acidothermus in the population showed an increasing trend. Altogether, the present findings demonstrate significant alterations in the structure and distribution of bacterial communities after sulfur induction treatment. Compared to other sulfur content, S1.5 kg/m3 treatment was resulted in more beneficial kiwifruit rhizosphere microbial composition changes.